Letters from Diarmuid Fásait [Fawsitt] to Florence O'Donoghue, regarding Liam De Róiste’s papers to be arranged by O'Donoghue, with seven letters from De Róiste to Fawsitt, 1948-1955, and notes by O'Donoghue - De Róiste, Liam, 1882-1959; Fawsitt, Diarmuid, 1884-1967; O'Donoghue, Florence, 1895-1967 (1948)
De Róiste’s letters mostly concern his series in the 'Cork Evening Echo', ‘Mar is cuimhin liom', 1954. Also includes list of members of Celtic Literary Society for 1902.
Keywords: De Róiste, Liam, -- 1882-1959; Celtic Literary Society; Cork Evening Echo; Ireland -- History -- 1922- -- Personal narratives; Ireland -- History -- Easter Rising, 1916